Martin the complete series - Carew, Topper 1943-; Bowman, John; Lawrence, Martin 1965-; Campbell, Tisha 1968-; Arnold, Tichina 1969-; Payne, Carl Anthony 1969-; Ford, Thomas Mikal 1964-2016 (Warner Bros. Entertainment Inc., 2020)
"Martin Lawrence (Bad Boys, Big Mommas House) plays Martin Payne, a brash radio personality who always speaks his mind, often to the frustration of Gina (Tisha Campbell), his feisty wife. His buddies Tommy and Cole are always on hand to lend support, especially when Martin locks his horns with Ginas loud-mouthed co-worker, Pam (Tichina Arnold). Then, of course, theres Martins overprotective mother, Mama Payne, his sassy-tongued next door neighbor, Sheneneh Jenkins, and the overbearing player, Jerome, all performed by Lawrence himself. Martin the Complete Series includes all the laughs from Seasons 1-5 and includes the series finale, when Martin and Gina must say good-bye." [DVD-container]
Staffeln 1-5
Orig.: USA, TV-Serie, Sitcom, 1992-1997
Keywords: Television series; Comedy films; Fernsehserie; Filmkomödie; African American radio broadcasters / Drama; African Americans / Drama; Television comedies; Comédies télévisées; African American radio broadcasters; African Americans; Television programs; Situation comedies (Television programs); Fiction television programs; Drama; Séries télévisées; Émissions télévisées; Comédies de situation; Fictions télévisées; DVD-Video